2013
DOI: 10.1136/bjsports-2013-092563
|View full text |Cite
|
Sign up to set email alerts
|

The Elbow-EpiTrainer: a method of delivering graded resistance to the extensor carpi radialis brevis. Effectiveness of a prototype device in a healthy population

Abstract: 'The Elbow-EpiTrainer: a method of delivering graded resistance to the extensor carpi radialis brevis. Effectiveness of a prototype device in a healthy population',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This is consistent with clinical recommendations for lateral epicondylalgia. 25 This study was limited by a small number of asymptomatic participants (only 3 had a past history of lateral epicondylalgia), and as such results are not necessarily generalizable to pathological populations. Indeed, a cross-sectional comparison between symptomatic and asymptomatic groups may be of interest, as morphological variation may predispose to lateral epicondylalgia.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with clinical recommendations for lateral epicondylalgia. 25 This study was limited by a small number of asymptomatic participants (only 3 had a past history of lateral epicondylalgia), and as such results are not necessarily generalizable to pathological populations. Indeed, a cross-sectional comparison between symptomatic and asymptomatic groups may be of interest, as morphological variation may predispose to lateral epicondylalgia.…”
Section: Discussionmentioning
confidence: 98%
“…They found that the above combination produced a graded increase in surface electromyography activity in the healthy ECRB [24]. However, clinical studies are currently being conducted to determine if this approach is effective in the treatment of LET.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published trial assessed the effectiveness of eccentric training of wrist extensors and supinator strengthening in healthy subjects [24]. They found that the above combination produced a graded increase in surface electromyography activity in the healthy ECRB [24].…”
Section: Discussionmentioning
confidence: 99%
“…Much of this is likely due to the realization of benefits of resistance training that is now recommended for the prevention and rehabilitation of disease and musculoskeletal injury [1,2,3,4,5]. Resistance exercise is known to have positive health effects on numerous tissues including heart [6], bone [7], skeletal muscle [8] and corticospinal [9] as well as hippocampal [10] nervous tissue.…”
Section: Accepted Manuscriptmentioning
confidence: 99%